Synthesis of conducting polymer by gamma Co-60 ray in aqueous solution - Le , Xuan Vinh; Nguyen , Ba Vu Chinh; Phan , Viet Cuong; Vo , Tai Dai; Trinh , Ngoc Dat; Dinh , Thanh Khan; Nguyen , Van Din (Nuclear Science and Technology, 2026)
This report presents the findings of a study on the synthesis of the conducting polymer poly(3,4-ethylenedioxythiophene) (PEDOT) using gamma Co-60 radiation in an aqueous solution saturated with N2 gas, containing 5 mM EDOT monomer and 0.2 M isopropanol. Gamma radiation with doses ranging from 12 kGy to 58 kGy from a gamma Co-60 source was employed. To assess the chemical composition of the solution before and after irradiation, UV-Vis and FTIR absorption spectra were examined. The results indicated the formation of yellow suspensions in the solution after irradiation, along with the emergence of dimers, oligomers, and PEDOT polymers as evidenced by UV-Vis spectra. The dried powders obtained from the irradiated solutions confirmed the successful synthesis of PEDOT, exhibiting distinct chemical structural characteristics in the FTIR spectra. These findings demonstrate the effective radiation-induced synthesis of conducting PEDOT polymer using gamma Co-60 irradiation.